Формування інтродукційної ценопопуляції Crocus reticulatus на ботаніко-географічній ділянці “Степи України” Національного ботанічного саду імені М. М. Гришка НАН України - Gritsenko, Victoria (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2020)
The research was carried out during Crocus reticulatus flowering time in 2002–2020 at the botanical-geographical plot “Steppes of Ukraine” of the M.M. Gryshko National Botanical Garden, National Academy of Sciences of Ukraine (NBG). Crocus reticulatus was introduced to the NBG from the natural habitats in 2002–2003. Ten generative individuals were planted in an area of 2 m2. The area of coenopopulation and the number of individuals increased gradually until 2018. In 2019–2020, there was a rapid increase in the covered area and number of individuals. However, the average density of individuals decreased. The percentage of pregenerative plants (juvenile, immature, and virginal) increased, and the percentage of generative individuals decreased. As of 2020, the area of introduced coenopopulation of C. reticulatus at the NBG reached 195 m2. It consists of 175 individuals (38 juvenile, 21 immature, 23 virginal, and 93 generative). The average density is 0.9 individuals per 1 m2. The spatial distribution of individuals is characterized as random and in groups. This is due to the predominance of the myrmecochoric and barochoric propagation. Indicators of the area, number, and average density of the introduced coenopopulation are within the normal ranges of the natural populations; however, they are smaller than those in maternal populations. The number of individuals of different age states and the number of individuals with one and two or three flowers in the introduced coenopopulation is close to such parameters of the natural population from Kyiv Plateau. Flowers of different colors were observed both in the introduced coenopopulation and in natural populations of C. reticulatus. As of 2020, the introduced coenopopulation of C. reticulatus is in the phase of logistic growth.